PENERAPAN COOPERATIVE LEARNING TIPE SNOWBALL THROWING UNTUK MENINGKATKAN AKTIVITAS DAN HASIL BELAJAR IPA/BIOLOGI SISWA KELAS VII SMP NEGERI 5 METRO T.P. 2011/2012 - Ariyanto, Asep; Achyani, Achyani (BIOEDUKASI (Jurnal Pendidikan Biologi), 2013)
Students’ learning achievement of SMP N 5 Metro heaven’t been accomplished thoroughly. Students were not active in learning process because the model of learning process is teacher centered, so students will be passive and it causes students’ learning achievement haven’t accomplished KKM (Criteria of Thoroughness Minimum) in school. The purpose of the research that is to improve learning achievement of nature science of seventh greade in SMP N 5 Metro academic year 2011/2012. Based on research data can be concluded that the impelementation of cooperative learning method by snowball throwing type can improve students’ learning achievement of seventh grade in SMP N 5 Metro academic year 2011/2012. The increasing of students’ learning achievement that be obtained from pra-PTK until second cycle is 34,04%. Based on that result, the researcher suggests to teacher to use this learning method in learning process. Kata Kunci: Snowball Throwing, Hasil Belajar.